Knowledge Management Through the TQM in the Metrology Area - Barragán-Ocaña, Alejandro; Olvera-Treviño, M. Ángeles; Urbina-Pérez, M. Gerson; Calderón-Álvarez, Darío; Nares-Hernández, J. Julio (IntechOpen, 2012)
None